Hemodynamic responses on prefrontal cortex related to meditation and attentional task - Deepeshwar, Singh; Vinchurkar, Suhas Ashok; Visweswaraiah, Naveen Kalkuni; Nagendra, Hongasandra RamaRao (Frontiers in Systems Neuroscience, 2015)
Recent neuroimaging studies state that meditation increases regional cerebral blood flow (rCBF) in the prefrontal cortex (PFC). The present study employed functional near infrared spectroscopy (fNIRS) to evaluate the relative hemodynamic changes in prefrontal cortex during a cognitive task. Twenty-two healthy male volunteers with ages between 18 and 30 years (group mean age ± SD; 22.9 ± 4.6 years) performed a color-word stroop task before and after 20 minutes of meditation and random thinking. Repeated measures ANOVA was performed followed by a post-hoc analysis with Bonferroni adjustment for multiple comparisons between the mean values of ‘During’ and ‘Post’ with ‘Pre’ state. During meditation there was an increased in oxy-hemoglobin (∆HbO) and total hemoglobin (∆THC) concentration with reduced deoxy-hemoglobin (∆HbR) concentration over the right prefrontal cortex (rPFC), whereas in random thinking there was increased ∆HbR with reduced total hemoglobin concentration on the rPFC. The mean reaction time was shorter in stroop color word task with reduced ∆THC after meditation, suggestive of improved performance and efficiency in task related to attention. Our findings demonstrated that meditation increased cerebral oxygenation and enhanced performance, which was associated with prefrontal cortex activation.